Analisis Faktor yang Mempengaruhi Customer Loyalty dalam Menggunakan Uang Elektronik Berbasis Server - Ni Made Mila Rosa Desmayani; I Gusti Agung Indrawan (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
Electronic money providers can be divided into two. First is a provider of electronic money from banks in the form of a physical chip card. Examples are e-money from Bank Mandiri and Flazz from BCA. The second is a server-based, non-banking e-money provider. Examples of products are GoPay, OVO and DANA. Competition is very tight to dominate the electronic money market share, encouraging server-based electronic money providers to compete to expand services, and provide facilities and discounts to its users. This has the potential to seize competitors' marketshare, where electronic money users will switch to other providers.  This article aims to analyze the factors that affect customer loyalty of server-based electronic money users in Denpasar, Bali. The object of this research is the factors that affects customer loyalty in using server-based electronic money. This research uses modified technology acceptance model. The collection of data on the perception of electronic money was carried out using a questionnaire. The results obtained from this questionnaire are: (1) perceived user convenience, (2) perceived usefulness, (3) perceived price suitability, (4) perceived discount has a positive dan significant effect on user loyalty in using server-based e-money.